Study on Cylindrical Source Theory Based on Vertical U-Tube Ground Heat Exchangers and It''''s Application - 杨卫波; 施明恒 (Zhileng xuebao)
Based on classic constant heat flux Cylindrical Source Theory,the variable heat flux Cylindrical Source Model of Vertical U tube was developed to simulate short time step long-term operation performance of GSHPS operating in variable heat transfer rate by quoting the idea of superposition principle and load aggregation. The present model was verified theoretically and experimentally with citing examples. The numerical simulation of heating performance of a Solar-earth source heat pump was performed with the improved Cylindrical Source model. The results indicate that the energy-saving rate of SESHPS is 8.3%-14.5% compared with ground source heat pump (GSHP) for application in Qingdao. The combined operation mode 2 with water tank in which the heated water flows through the solar collector first and then through the buried coil is preferable. The area of solar-collector and the length of buried ground coil can be calculated respectively either by the energy ratio of 63% to 37% or by size ratio of 13.8m to 1m2. In addition,SESHPS may be economically viable only when the price of solar collector per square meters is smaller than the drilling cost of 5.81 m length.